Female leadership and Its repercussions on employees’ motivation in Portugal - Reis, Felipa Lopes dos (2022)
The type of leadership is a factor that has proven to be fundamental to employee motivation and satisfaction in the workplace. This study aimed to analyse whether female leadership has repercussions on the motivation of employees in the labour market. Based on a case study (labour market) including a questionnaire and an interview, a representative sample was obtained, and the following topics were addressed: quality of the relationship between leader-employee; satisfaction and motivation of employees at work; female leadership. The evidence obtained allows us to conclude that the variables under study, such as leadership and the quality of the leaderemployee relationship, are not positively related to either employee job satisfaction or employee motivation at work.